User guide for ADB statistical business register. (Metro Manila, Philippines Asian Development Bank, 2018)
This user guide provides step-by-step instructions on how to set up, use, and maintain the statistical business register of the Asian Development Bank (ADB).It also outlines the key technical considerations that guided ADBs development of the software. This publication serves as a reference for countries looking to establish statistical business registers of their own using the software solution developed as part of this initiative. Statistical business registers are structured databases that provide information on business establishments and their activities, enabling a country national statistical system to produce economic statistics and indicators. This helps governments design and implement economic policies that are data-driven.
Keywords: Economics -- Statistical methods